Associations of five obesity metrics with epigenetic age acceleration: Evidence from 2, 474 Taiwan Biobank participants. Issue 10 (2nd September 2021) - Lin, Wan‐Yu; Wang, Yu‐Cyuan; Teng, I‐Hsuan; Liu, Chi; Lou, Xiang‐Yang
Abstract: Objective: Obesity is associated with epigenetic age acceleration (EAA), resulting in an increased risk of many age‐related disorders. However, most studies have focused on the relationship of EAA with BMI. Whether any other obesity metric is more relevant to EAA remains unknown. Methods: Here, the methylation ages of 2, 474 Taiwan Biobank (TWB) participants were calculated according to Levine's phenotypic age (PhenoAge) and Lu's GrimAge. Residuals from regressing methylation age on chronological age were used to quantify PhenoEAA and GrimEAA. Five obesity metrics were evaluated, namely BMI, body fat percentage, waist circumference, hip circumference, and waist‐hip ratio. Sex‐stratified EAA was regressed on each of the five obesity metrics. Results: For male individuals, an increase of one SD in waist‐hip ratio (0.06) was associated with a 0.602‐year PhenoEAA ( p = 6.3E‐6) and a 0.481‐year GrimEAA ( p = 1.2E‐8). For female individuals, every SD increase in BMI (3.7 kg/m 2 ) was associated with a 0.600‐year PhenoEAA ( p = 3.3E‐5) and a 0.305‐year GrimEAA ( p = 3.1E‐5). Conclusions: "Abdominal obesity" and "general obesity" are significantly associated with male and female EAA, respectively. The prevention of abdominal obesity and general obesity is associated with a lower risk of EAA in men and women, respectively.